Exploring the Hospital Performance during the COVID-19 Pandemic from the Perspective of Intellectual Capital: An Empirical Study of Taipei Hospital in Taiwan - Hsiung, Hsing-Hua; Lin, Yu-Jie (Journal of Ecohumanism, 2024)
The COVID-19 pandemic, starting in 2019, posed unprecedented challenges to global healthcare systems, with Taiwan's rapid response gaining notable attention (Cheng, Li, & Yang, 2020). This paper examines how non-profit hospitals can improve crisis management capabilities, using Taipei Hospital as an empirical study. It proposes a framework for constructing an intellectual capital report based on the ARC model, enhancing traditional financial statements with a comprehensive view of the hospital's intangible assets. Employing Data Envelopment Analysis (DEA) to evaluate Taipei Hospital's operational performance from 2013 to 2023, the study finds that the hospital's operational efficiency during the pandemic exceeded pre-pandemic levels, demonstrating its ability to leverage the crisis for improvement. This supports the assertion that intellectual capital is crucial for research and development organizations, validating the proposed reporting framework.